2014
DOI: 10.1002/ijc.29327
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of homologous recombination sensitizes human tumor cells to IGF‐1R inhibition

Abstract: Inhibition of type 1 IGF receptor (IGF-1R) sensitizes to DNA-damaging cancer treatments, and delays repair of DNA double strand breaks (DSBs) by non-homologous end-joining and homologous recombination (HR). In a recent screen for mediators of resistance to IGF-1R inhibitor AZ12253801, we identified RAD51, required for the strand invasion step of HR. These findings prompted us to test the hypothesis that IGF-1R-inhibited cells accumulate DSBs formed at endogenous DNA lesions, and depend on residual HR for their… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
13
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 24 publications
3
13
1
Order By: Relevance
“…BRCA2 is a key mediator of repair by homologous recombination (HRR) and recruits RAD51 to the DNA damage site: cells that express defective BRCA2 are unable to form RAD51 foci after irradiation [44] . Previous reports have demonstrated that depletion of BRCA2 sensitizes cells to IGF-1R inhibition and that RAD51 foci formation is reduced, indicating defective HRR [45] . BRCA2 undergoes epistatic interactions with four RAD51 paralogs, and its loss alone can affect the HRR [46] .…”
Section: Discussionmentioning
confidence: 95%
“…BRCA2 is a key mediator of repair by homologous recombination (HRR) and recruits RAD51 to the DNA damage site: cells that express defective BRCA2 are unable to form RAD51 foci after irradiation [44] . Previous reports have demonstrated that depletion of BRCA2 sensitizes cells to IGF-1R inhibition and that RAD51 foci formation is reduced, indicating defective HRR [45] . BRCA2 undergoes epistatic interactions with four RAD51 paralogs, and its loss alone can affect the HRR [46] .…”
Section: Discussionmentioning
confidence: 95%
“…Despite the strong rationale around IGF-1R pathway inhibition, the promising preclinical data and its reasonable tolerability, the clinical efficacy has been disappointing [ 49 , 50 ]. Our study shows that cells with HR deficiency are more sensitive to IGF-1Rki, suggesting that this subset of patients could benefit from this targeted therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Traditional chemotherapy, in particular platinum-based compounds, targets rapidly dividing cells primarily by inducing DNA damage. Pre-clinical studies suggest IR/IGF-IR signaling protects cells from DNA damage and induces DNA damage repair via non-homologous end joining (NHEJ) and homologous repair ( 129 , 130 ). Consistent with this, inhibition of IGF-IR causes sensitization to cisplatin ( 98 , 131 , 132 ), doxorubicin, and trabectedin ( 133 ), as well as ionizing radiation ( 129 , 134 136 ) in ovarian, prostate, colon, and breast cancer cells and in mouse xenograft models.…”
Section: Insulin/igf Connection To Cancermentioning
confidence: 99%